Extracellular vesicles in oral squamous cell carcinoma: current progress and future prospect - Zhang, Yanqi; Liu, Jianing; Liu, Shiyu; Yu, Lu; Liu, Siying; Li, Meng; Jin, Fang (Frontiers in Bioengineering and Biotechnology, 2023)
Oral squamous cell carcinoma (OSCC) is the most aggressive oral and maxillofacial malignancy with a high incidence and low survival rate. OSCC is mainly diagnosed by tissue biopsy, which is a highly traumatic procedure with poor timeliness. Although there are various options for treating OSCC, most of them are invasive and have unpredictable therapeutic outcomes. Generally, early diagnosis and noninvasive treatment cannot be always satisfied simultaneously in OSCC. Extracellular vesicles (EVs) are involved in intercellular communication. EVs facilitate disease progression and reflect the location and status of the lesions. Therefore, EVs are relatively less invasive diagnostic tools for OSCC. Furthermore, the mechanisms by which EVs are involved in tumorigenesis and tumor treatment have been well studied. This article dissects the involvement of EVs in the diagnosis, development, and treatment of OSCC, providing new insight into the treatment of OSCC by EVs. Different mechanisms, such as inhibiting EV internalization by OSCC cells and constructing engineered vesicles, with potential applications for treating OSCC will be discussed in this review article.